Automatyka, sterowanie, zarządzanie : książka jubileuszowa z okazji 70-lecia urodzin profesora Kazimierza Mańczaka * Interpretacja ocen zmiennych parametrów estymowanych jako parametry stałe - Nahorski, Zbigniew (1945– ); Weryński, Andrzej (Instytut Badań Systemowych. Polska Akademia Nauk, 2002)
Estimation of constant parameters in the homogeneous differentia[ equation models of systems with time varying but bounded parameters is considered. In this case the parameter estimates can take any value within bounds. In the first order models the estimates converge to the mean values or to the weighted mean values, depending on the methodology of estimation. In the higher order models this problem may be more complicated. For the periodically varying parameters a good policy to estimate the mean value is to observe the system with the constant period of parameters ' variation. Other observation schemes may lead not only to biased estimates of the parameters but also to biased estimate of the system order when it is estimated statistically. Examples of modelling problems connected with the varying parameters encountered in real systems are presented.
[1-2], 283-307 stron ; 21 cm
Bibliografia s. 306-307